2020
DOI: 10.1021/acschemneuro.0c00478
|View full text |Cite
|
Sign up to set email alerts
|

An α-Cyanostilbene Derivative for the Enhanced Detection and Imaging of Amyloid Fibril Aggregates

Abstract: The aggregation of proteins into amyloid fibrils has been implicated in the pathogenesis of a variety of neurodegenerative diseases, including Alzheimer's and Parkinson's disease. Benzothiazole dyes such as Thioflavin T (ThT) are well characterised and widely used fluorescent probes for monitoring amyloid fibril formation. However, existing dyes lack sensitivity and specificity to oligomeric intermediates formed during fibril formation. In this work we describe the use of an α-cyanostilbene derivative with agg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…It emitted green fluorescence in the presence of amyloid aggregation while no emission could be observed at the monomer state. Similar results were found in the investigations of TPE-TPP [107] and ASCP [108], which contained no amyloid-like structures as targeting moieties.…”
Section: Neurodegenerative Diseasesupporting
confidence: 88%
“…It emitted green fluorescence in the presence of amyloid aggregation while no emission could be observed at the monomer state. Similar results were found in the investigations of TPE-TPP [107] and ASCP [108], which contained no amyloid-like structures as targeting moieties.…”
Section: Neurodegenerative Diseasesupporting
confidence: 88%
“…Additionally, it was found to be fluorogenic in the presence of amorphous aggregates and can detect oligomeric species formed early during aggregation. [ 178 ] 119 [ 179 ] and 120 [ 180 ] (Figure 20) are acrylonitrile‐related compounds with potential as fluorescent imaging agents for A β detection.…”
Section: Biological Activities Of Acrylonitrilesmentioning
confidence: 99%
“…Meanwhile, problems such as small Stokes shift and poor sensitivity are also the disadvantages of ThT. 17,24…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, problems such as small Stokes shift and poor sensitivity are also the disadvantages of ThT. 17,24 In 2001, Tang's group discovered the aggregation-induced emission (AIE) properties of some luminogens. 25 So far, several studies associated with AIE have been reported on the detection of amyloid fibrils including insulin, Ab 42 and lysozyme.…”
Section: Introductionmentioning
confidence: 99%